[Samaan Tree] - (:unkn) unknown (My University, 2010)
A full grown Samaan Tree in a savannah in Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; [1940]; Savannas--Trinidad and Tobago; Parks--Trinidad and Tobago; Fences--Trinidad and Tobago; Electric lines--Trinidad and Tobago; Overhead electric lines--Trinidad and Tobago; Electric power distribution--Trinidad and Tobago; Shade trees--Trinidad and Tobago